Osteomyelitis following Domestic Animal Bites to the Hand: Two Case Reports and Practical Guidelines - Jung Soo Lim (Archives of Plastic Surgery, 2016)
Recently, the number of cases of animal bite wounds has increased significantly in concordance with an increase in the pet population around the world. The authors report two rare cases of osteomyelitis of the phalanx following cat and dog bites. On initial physical examination, signs of a severe infection were observed. Radiographs of both patients showed the presence of osteomyelitis, and in one of the patients, the diagnosis was confirmed with a bone biopsy. After use of empirical antibiotics, intravenous antibiotic therapy that matched the identified bacterium's sensitivity was initiated, and at the same time, secure dressing including debridement was performed to induce secondary healing. In addition, the patients were closely monitored with serial X-rays, and culture and blood test follow-up. One patient fully recovered without sequelae, but the other patient suffered a loss of distal interphalangeal joint motion. When dealing with bite wounds located on the hand, it is important to visit the hospital as soon as possible and receive the appropriate treatment early. Moreover, to prevent severe complications such as osteomyelitis, it is important to administer antibiotic therapy to which the cultured bacteria are sensitive, along with proper wound management and prophylactic antibiotic treatment.